PENGARUG BUDGETARY GOAL CHARACTERISTICS TERHADAP KINERJA APARAT PEMERINTAH DAERAH KABUPATEN BREBES - Aditya, Faisal; Suwarti, Titiek (Proceeding Fakultas Ekonomi, 2012)
The purpose of this research is to anabze the effect of the budgetary goal characteristics that is the budgetary participation, the clearance of budgetary goal, budgetary feedback and budgetary evaluation to the performance of Civil Servants in Brebes Territory. By using the purposive sampling technique from 375 the level 3 and 4 esselon civil servants this research choose 67 ojicials who become the samples. This research /ind that 53,7 % independent variables have contribution to the change of Peqfomance of the Civil Servants in Brebes Territory. Simultanousb/ the four variables have sigrzyicant effect to the Pejomance of the Civil Servants in Brebes Territory. Partialbr the budgetary participation and the budgetary feedback have no signyicant ejfect to the Perfomance ofthe Civil Servants in Brebes. Only the clearance of budgetary goal and budgetanv evaluation have signyicant positive effect to the performance of government ojicial in Brebes Terri tory. Keywords: Budgetary Participation; Clearance of Budgetary Goal; Budgetary Feedback; Budgetary Evaluation; Performance of Government Ujicial